Penerapan Pendekatan Komunikatif dalam Meningkatkan Keterampilan Berbicara Bahasa Inggris (Studi Kasus Pembelajaran Bahasa Inggris dalam Perspektif Pendidikan Nilai) - Suharyanto H. Soro; Jana Ermya; Joko Salman (LP. Ma'arif Janggan Magetan, 2023)
The communicative approach is one (option) that can be used in learning by teachers to their students in order to transfer knowledge (cognitive domain) as provision in navigating world life. Each approach to learning has advantages and disadvantages so that teachers are required to be creative in delivering teaching material. This study aims to describe the application of a communicative approach in learning so that it can improve students' English speaking skills. Researchers use a case study approach. Methods of data collection using observation and interview methods. The samples in this study were taken by purposive sampling. The results of the research findings indicate that the application of a communicative approach in learning English carried out by teachers can improve students' speaking skills. In the educational value perspective, this approach focuses on students' performance so that they can form habits in using English as a foreign language in communication interactions.